EKSISTENSI TIRTHA PENGENTAS DI PURA MAKSAN GEDE DESA KUBUTAMBAHAN KECAMATAN KUBUTAMBAHAN KABUPATEN BULELENG - wayan Sunampan (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2022)
Tirtha pengentas is one of the means in the ceremony of giving. In general, tirtha pengentas are usually made by a sulinggih. However, it is different from the existing tirtha pengentas in Kubuaddan Village, Kubuaddan District, Buleleng Regency. In the process of the pitra yadnya ceremony, tirtha trimmers were obtained at the Maksan Gede Temple. Based on this problem, a research was conducted by focusing on the existence of tirtha penetas at Maksan Gede Temple, Kubuaddan Village, Kubuaddan District, Buleleng Regency. This study has a purpose to describe the existence of tirtha penetas by using theories and methods in analyzing data. The discussion of this research is about the Maksan Gede Temple as a place for the procurement of tirtha pengentas. Maksan Gede Temple is one of the temples in Kubutambahan Village, Kubutambahan District, Buleleng Regency. The structure of this temple consists of a tri mandala. The facilities used in conducting tirtha pengentas are water, reeds, gold pieces, sandalwood. The ceremonial facilities used are in the form of a sacred offering which is offered to Ratu Gede Shiva to ask for tirtha of the pengentas. The process of holding tirtha pengentas begins with preparing ceremonial facilities by both Jro Mangku and Jro Serati. After all the facilities are ready then jro mangku will do piuning to ask for tirtha to Ratu Gede Shiva which is also followed by the local community. When it is finished, the alleviation tirtha will be taken to the place of worship. Based on this description, it can be concluded that tirtha alleviation is not only made by a sulinggih. Tirtha reducer also has various functions.Keywords: Existence, Tirtha pengentas, Maksan Gede Temple